EDITORIAL - Philip, Susan (SARE: Southeast Asian Review of English, 2024)
EDITORIAL: Minorities Speak Up This is not a special issue – and yet, entirely unplanned, we have a slate of articles which focus on minorities and how they resist authoritative impositions, whether in relation to ethnicity or gender or sexuality. Perhaps this reflects the zeitgeist. In a global landscape where minority rights and autonomy are increasingly under threat (think, for example, of the chilling slogan “Her body, my rights”), and where homeland and belonging are often precarious concepts at best (what does ‘home’ mean for Palestinians? Where is home for refugees and other displaced persons?), literature offers a space for acts of resistance. The fact that all five of the articles in this issue are concerned with acknowledging and centering this resistance in some form, speaks to the urgency and currency of these matters.